Oral Health of Children and Adolescents in the United Arab Emirates: A Systematic Review of the Past Decade - Al Anouti, Fatme; Abboud, Myriam; Papandreou, Dimitrios; Haidar, Suzan; Mahboub, Nadine; Rizk, Rana (Frontiers in Oral Health, 2021)
Oral diseases are a universal public health problem with serious health and economic burdens. These diseases are a major concern in the pediatric population specifically. In the United Arab Emirates (UAE), among all the diseases that affect children, oral diseases, particularly early childhood caries, are the most common despite improvement in the provision of oral health services. Enhancing oral health status is one of the key public health goals in the country. This current systematic review aims to summarize the available data on oral health among children and adolescents in the UAE over the past decade (2011–2021). The review was conducted following a predefined protocol and in concordance with the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) statement. PubMed, the Cumulative Index to Nursing and Allied Health Literature (CINAHL) via EBSCO, EMBASE via Ovid, the Cochrane Library, and the Index Medicus for the Eastern Mediterranean Region (IMEMR) databases, and the gray literature were searched for original studies reporting on oral health in the pediatric population in the UAE, without applying any language restriction. Twenty-nine studies were included reporting on a total of 43,916 participants; they were mostly cross-sectional, and emirate-based; they were mostly limited by their setting and convenient sampling. Among the general pediatric population, results showed a high prevalence of dental caries across different emirates. Nevertheless, it was difficult to provide a predictable profile of caries, as risk factors were not well-explored and inconsistent across studies. Suboptimal oral hygiene practices were also prevalent, in addition to a low utilization of dental services. Furthermore, included studies showed a high level of oral problems in children with different disease (down syndrome, cerebral palsy, thalassemia, autism…) and special conditions (children in prison nurseries); yet, in general, treatment indices were lower than their healthy counterparts. This review suggests that dental caries is a major pediatric health problem in the UAE. Risk factors included higher consumption of snacks, being in public schools, lower maternal education level, and socioeconomic status. Nevertheless, risk factors were not well-explored and inconsistent across studies. Suboptimal oral hygiene practices and a low utilization of dental services were also identified, in addition to a high level of oral problems in children with different disease coupled with lower treatment indices in comparison with their healthy counterparts. This systematic review provides crucial information for planning and evaluating effective oral health programs, identifies gaps in the recent research in this field, and paves the way for preventive and interventional studies targeting oral health in pediatrics in the UAE. Immediate oral health promotion strategies are needed to address this public health problem early in its course by creating conditions that promote oral health, and increasing uptake of dental services. Intensifying research to draw temporal trends, understand the profile of childhood caries in the UAE, and explore cost-effective national community prevention programs are also needed.